Change and Development of A Quality Culture In Madrasah - Hadi, Edi Nanang Sofyan (Journal of Quality Assurance in Islamic Education (JQAIE), 2023)
This study explores concepts related to effective madrasah head leadership in building and developing a quality culture. The type of literature study research is used to explain the results of existing studies. Data were obtained from various relevant literature sources, such as books and journals, which contained information following the focus of the study, namely the leadership of the head of the Madrasah and the culture of quality. The data obtained is then carried out for content analysis. In addition, in maintaining the suitability of the review process and preventing and overcoming misinformation, checks are carried out between libraries, re-read the literature, and pay attention to expert comments. The results showed that ten indicators must be owned by school principals so that the development of a quality culture can run effectively, namely: complete vision, responsibility, example, empowering staff, listening to others, providing excellent service, developing people, empowering madrasahs, focusing on students, and management that prioritizes practice. Therefore, the critical roles of school principals must continue to be pursued, including as educators, managers, administrators, supervisors, leaders, innovators, and motivators. By integrating this critical role, it can be ensured that the quality culture of the Madrasah can be realized immediately.